Inflammatory bowel disease and risk of mortality in COPD. Issue 5 (12th February 2016) - Vutcovici, Maria; Bitton, Alain; Ernst, Pierre; Kezouh, Abbas; Suissa, Samy; Brassard, Paul
Patients with chronic obstructive pulmonary disease (COPD) have higher incidence and prevalence of other chronic inflammatory diseases, including inflammatory bowel disease (IBD). We assessed whether IBD onset increases mortality risk in patients with COPD or asthma-associated COPD. Two population-based cohorts of COPD and asthma-COPD subjects were identified using the administrative health databases in Québec, Canada, 1990–2007. Death records were retrieved from the death certificate registry. Cox proportional hazards models were used to assess the impact of newly developed IBD on mortality risk. The COPD and asthma-COPD cohorts included 273 208 and 26 575 patients, respectively, of which 697 and 119 developed IBD. IBD increased the risk of all-cause mortality in both COPD (hazard ratio 1.23, 95% CI 1.09–1.4) and asthma-COPD (hazard ratio 1.65, 95% CI 1.23–2.22). In asthma-COPD patients, IBD increased the risk of mortality from respiratory conditions (hazard ratio 2.18, 95% CI 1.31–3.64); in COPD patients, IBD increased the risk of death from digestive conditions (hazard ratio 4.45, 95% CI 2.39–8.30). IBD is a risk factor for mortality in patients with pre-existing COPD or asthma-COPD. IBD increased mortality by respiratory and digestive conditions in patients with asthma-COPD and COPD, respectively. IBD is a risk factor for mortality in patients with pre-existing COPD or asthma-associated COPD http://ow.ly/X6PaY